Gut microbiota differs between two cold-climate lizards distributed in thermally different regions - Jun-Qiong Chen; Lu-Wen Zhang; Ru-Meng Zhao; Hai-Xia Wu; Long-Hui Lin; Peng Li; Hong Li; Yan-Fu Qu; Xiang Ji (BMC Ecology and Evolution, 2022)
Abstract Background The metabolic cold-climate adaption hypothesis predicts that animals from cold environments have relatively high metabolic rates compared with their warm-climate counterparts. However, studies testing this hypothesis are sparse. Here, we compared gut microbes between two cold-climate lizard species of the genus Phrynocephalus to see if gut microbiota could help lizards adapt to cold environments by promoting metabolism. We conducted a 2 species (P. erythrurus and P. przewalskii) × 2 temperatures (24 and 30 °C) factorial design experiment, whereby we kept lizards of two Phrynocephalus species at 24 and 30 °C for 25 d and then collected their fecal samples to analyze and compare the microbiota based on 16S rRNA gene sequencing technology. Results The gut microbiota was mainly composed of bacteria of the phyla Proteobacteria, Firmicutes, Bacteroidetes, and Verrucomicrobia in both species (Proteobacteria > Firmicutes > Verrucomicrobiota in P. erythrurus, and Bacteroidetes > Proteobacteria > Firmicutes in P. przewalskii). Further analysis revealed that the gut microbiota promoted thermal adaptation in both lizard species, but with differences in the relative abundance of the contributory bacteria between the two species. An analysis based on the Kyoto Encyclopedia of Genes and Genomes revealed that the gut microbiota played important roles in metabolism, genetic information processing, cellular processes, and environmental information processing in both species. Furthermore, genes related to metabolism were more abundant in P. erythrurus at 24 °C than in other species ⋅ temperature combinations. Conclusion Our study provides evidence that gut microbiota promotes thermal adaptation in both species but more evidently in P. erythrurus using colder habitats than P. przewalskii all year round, thus confirming the role of gut microbiota in cold-climate adaptation in lizards.